COVID-19 and HIV/AIDS in a cohort study in Sao Paulo, Brazil: outcomes and disparities by race and schooling. Issue 7 (3rd July 2022) - Rocha, S. Q.; Avelino-Silva, V. I.; Tancredi, M. V.; Jamal, L. F.; Ferreira, P. R. A.; Tayra, A.; Ferreira, P. M.; Carvalhanas, T.; Domingues, C. S. B.; Souza, R. A.; Gianna, M. C.; Kalichman, A. O.; et al.
ABSTRACT: Studies describing characteristics and outcomes of COVID-19 among people living with HIV are currently limited, lacking detailed evaluation of the interplay among demographics, HIV-related variables, and comorbidities on COVID-19 outcomes. This retrospective cohort study describes mortality rates overall and according to demographic characteristics and explores predictors of admission to intensive care unit and death among 255 persons living with HIV with severe acute respiratory syndrome and confirmed SARS-CoV-2 infection in the State of Sao Paulo, Brazil. We found that the overall mortality rate was 4.1/1, 000 person-days, with a case-fatality of 34%. Higher rates occurred among older adults, Black/Mixed skin color/race patients, and those with lower schooling. In a multivariable analysis adjusted for age, sex, CD4 count, viral load and number of comorbidities, skin color/race, and schooling remained significantly associated with higher mortality. Although tenofovir use was more frequent among survivors in the univariable analysis, we failed to find a statistically significant association between tenofovir use and survival in the multivariable analysis. Our findings suggest that social vulnerabilities related to both HIV and COVID-19 significantly impact the risk of death, overtaking traditional risk factors such as age, sex, CD4 count, and comorbidities.